Peningkatan Hasil Belajar Siswa Melalui Kooperatif Picture And Picture: Suatu Studi di SDN 5 Menteng - Andi Wahyudi; Berth Penny Pahan; Ratih Sulistyowati (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
The picture and picture type cooperative learning models is an appropriate learning model in developing student creativity, generating is a sense of fun during learning by arranging pictures in the correct order. This research uses quantitative approach with experimental research data analysis with descriptive statistics and inferential statistics and hypothesis testing to see the influence of two variables with the t-test. The aims of this research are 1). To determine the effect of the picture and picture type cooperative learning model on the learning outcomes of class III-B students 2). To compare picture and picture type cooperative learning model with lecture model on the learning outcomes of class III-B students at Junior High School 5 Menteng Palangka Raya. The results of this research in the paired sample t-test show a 2-tailed sig result of 0.00 < 0.05, so There is an influence of the picture and picture model on student learning outcomes and the independent sample t-test obtained a result of 0.01 < 0.05. So it can be concluded that there is an influence of the picture and picture cooperative learning model on student learning outcomes compared to the lecture model.